Optimizing Education Services: Strategy for Implementing the BPOPP Program in Supporting School Operations - Kusnul Azizah; Ana Sopanah; Indah Dewi Nurhayati (Innovation Business Management and Accounting Journal, 2024)
Accounting is closely related to financial information which is used as a basis for making decisions in everyday life. Accounting also consists of various types, one of which is educational accounting. In educational accounting there are several aspects, including the school budget, school infrastructure, school management, participation from parents, implementation accountability funds. The school budget comes from educational assistance provided by the government to improve the quality of education. BPOPP is a form of educational program provided by the East Java Provincial government to improve the quality of education. BPOPP is implemented in accordance with the Technical Guidelines and applicable Governor Regulations. At SMKN 9 Malang, procedures for using funds and reporting procedures for BPOPP at SMKN 9 Malang are good, although implementation still encounters several obstacles. In the future, it is hoped that there will be changes in the Technical Technical Guidelines and applicable Governor's Regulations so that the realization of BPOPP can be maximized.